The Efficiency Analysis of Medical Records Departments of Tehran University of Medical Sciences Hospitals with Data Envelopment Analysis (2007-2009) - M Yousefi; S Fazaeli; R Safdari; N Masuri; H Dargahi (Tehran University of Medical Sciences, 2010)
Background and Aim: Analysis of efficiency in hospitals, as the most expensive operating unit of the health system, is very important. This costly unit has several departments that one of them is medical records. This study is trying to analyze the efficiency of medical records department for the enhancement of using medical records facilities.Materials and Methods: In this study, technical, scale and managerial efficiency of medical records department has been studied by data envelopment analysis method, and assuming the scale efficiency variable and the input axis. Information used in this study was the input variables (number of technician personnel and lower and Master of Science personnel and higher), output variables (number of emergency and outpatient and inpatient medical records and the number of filing unit visitors to respond) during 2007-2009.Results: The average technical efficiency of medical records departments is 84 percent, that indicates there is at least 16 percent capacity for an increase in performance. Average of management and scale Performance in units during the 3 years of study are 95 and 89 percent respectively. Most input surplus is relevant to technician and lower personnel. The average performance of these units in general hospitals is 80 percent and in specialized activities is 92 percent.Discussion and Conclusion: Relationship between studied indicators in this study with performance medical records departments showed that using such as employee personnel with undergraduate degrees and higher and educated in medical records filed, the use of managers with enough experience in this department and more use of computer systems for unit activities can fill 16 percent capacity of performance improvement in these units.